The Fetal Care Team: Care for Pregnant Women Carrying a Fetus with a Serious Diagnosis. Issue 6 (November 2016) - Loyet, Margaret; McLean, Amy; Graham, Karen; Antoine, Cheryl; Fossick, Kathy
Abstract: Background: Women carrying a fetus with a suspected or known fetal anomaly have complex needs such as emotional and informational support and help with the logistical aspects of arranging care and treatment from numerous specialists. Improvement in Quality of Care for Women Carrying a Fetus with a Suspected or Known Fetal Anomaly: Our fetal care team was initiated in 2012 to meet the needs of this high-risk pregnant population. The fetal care team nurse coordinator supports the woman and her family through all aspects of care during the pregnancy and neonatal period including scheduling appointments with multiple specialists, being there with her as a support person, keeping her updated, making sure she has accurate information about the fetal diagnosis, and helping her to navigate the complex healthcare system. Results: Since the program was started, the number of women enrolled has nearly doubled. Women overwhelmingly are satisfied with the various services and care provided by the nurse coordinators and believe the fetal care team has value for them. Clinical Implications: We present the development and operations of our fetal care team with a focus on the role of the fetal care team nurse coordinator. Abstract : When pregnant women learn their fetus has a diagnosis of a serious or lethal anomaly, a coordinated multidisciplinary team approach can offer much needed support, information, and navigation through the complex health system. Registered nurse fetal care team coordinators assist women and their families at this perinatal center when the pregnancy does not go as expected. Descriptions of their roles as part of the fetal care team and the service they provide are presented.